Comparison of Brazilian and U.S. biofuel demand: The role of vehicle fleets and prices in meeting policy targets - Tokgoz, Simla; Bhandary, Prapti (Walter de Gruyter GmbH, 2011)
The two largest producers of biofuels in the world, Brazil and U.S., both have various policy initiatives designed to meet a significant portion of their need for transportation fuels from biofuels. However, the structure of bio biofuel demand and vehicle fleets varies widely between these two economies, affecting the level of absorption of biofuels by the refiners and final consumers of each country. The relative prices of biofuels to conventional fuel prices (gasoline and diesel) determine consumers' demand not only for biofuels and but also for alternative fuel vehicles. The vehicle fleet structure, in turn, determines the ability of the transportation sector to absorb biofuels. Brazil, with its low costs of production, can sell ethanol at a competitive level with gasoline, which allows ethanol demand to expand and vehicle fleet to transform. U.S., on the other hand, cannot sell ethanol competitively. This limits market expansion and vehicle fleet transformation in the U.S., which, in turn, hinders its ability to achieve policy targets. With many countries taking initiatives to meet a large share of their transportation fuel needs from biofuels, the experiences of U.S. and Brazil provide valuable lessons for policy makers, where an in-depth analysis of the inter-linkages among relative prices, biofuel demand, and vehicle fleet structure prove to be crucial for successful and effective policy making.